Performance and Continuity Prospect of Sub Terminal Agribisnis Sewukan, Kabupaten Magelang in Increasing Farmerâ€™s Wealth in Merapi Merbabu Area after Merapi Eruption - Lestari, Puji (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
The concept of Agribusiness Subâ€Terminal (Sub Terminal Agribisnis/STA) was established to solve the inefficient marketing of agricultural commodities. The Government of Magelang Regencydeveloped STA Sewukan in the region of Merapi Merbabu. The research concluded that STA Sewukan performed well in improving farmerâ€™s livelihood in the Merapi Merbabu region. The variables employed to evaluate the performance included marketing channel, marketing margins,Â  share for the farmers, market structure, farmerâ€™s income and institutional aspect. Located on the slopes of Mount Merapi, STA Sewukan has been affected by Merapi eruption on October 26th 2010. However, adaptability of the people maintained the existence of STA Sewukan. Therefore, the study concluded that sustainability of STA Sewukan can be achieved by (1) restoring damaged access to STA Sewukan caused by the eruption; (2) strengthening the resilience from Mount Merapi eruption; (3) maintaining the positive performance indicators such as farmerâ€™s share, market structure, and farmerâ€™s income; (4) increasing the performance by improving marketing channel efficiency, reducing marketing margin, and strengthening institutional support.